Tango in modern dance - Lu Bonan (ХДАК, 2024)
As one of the five standard dance styles, tango dance features a combination of movement and stillness, explosiveness, and aggression. The most prominent feature of tango dance steps is the “crab cat step”. Tango dance is different from the other four dances in that it often moves in a low position, with a sense of power extending downwards. The foot movements are fast and powerful, constantly changing the center of gravity, and the styling movements are full of power. Tango is a dance form that originated in Argentina and is considered the most Latin inspired form of modern dance. It combines the elegance of European court dance with the passion of South American dance, showcasing unique dance movements. It is usually considered a passionate and passionate dance, and is highly popular.
Keywords: бальні танці